Factors influencing personal financial practices of postgraduate students at universities in Kota Kinabalu, Sabah - Rudy Ansar (2014)
The purpose of this study is to examine factors influencing personal financial practices of postgraduate students at universities in Kota Kinabalu, Sabah such as Universiti Malaysia Sabah (UMS), Universiti Tun Abdul Razak (UNITAR), Universiti Teknologi Mara (UiTM) and Open University Malaysia (OUM). The study covers both full-time and part-time postgraduate students, who are working, have own income and studying at the same time. From the result of data analyses done, this study has conduded demographic variables: occupation and income have significant influenced postgraduate students upon practicing their personal financial practices of investment. Furthermore, money attitude of retention-time have significant and positive relationship with personal financial of investment and planning. In addition, money attitude of retention-time have significant and negative relationship with personal financial practices of cash management. Moreover, money attitude of distrust has significant and positive relationship with personal financial practices of planning but not significant to personal financial practices of investment and cash management. While Money attitude of power-prestige has significant and have negative relationship with personal financial practices of planning.